Service Quality Priorities at Purabaya Bus Terminal Using Service Quality, Model Kano, and 5 Why’s - Simanjuntak, Vanesha Natalaya Meisani; Aryanni, Enny (Academia Open, 2026)
General Background: Service quality is a critical determinant of passenger satisfaction in public transportation terminals. Specific Background: Purabaya Type A Bus Terminal plays a strategic role in supporting mobility in Surabaya, yet several service attributes remain below passenger expectations. Knowledge Gap: Previous studies have primarily measured passenger satisfaction without integrating service quality assessment, service attribute classification, and root cause analysis into a unified framework. Aims: This study aimed to identify priority service attributes requiring improvement and formulate appropriate improvement strategies using the Service Quality (SERVQUAL), Kano Model, and 5 Whys methods. Results: A quantitative study involving 96 passengers found an overall service quality score of 0.78 (Q < 1), indicating that existing services have not met passenger expectations. Eight priority attributes were identified, including bus operational standards, toilet cleanliness, schedule punctuality, prayer facilities, waiting room facilities, trusted bus operators, complaint responsiveness, and terminal security. These attributes were classified as Must-be in the Kano Model, indicating fundamental passenger requirements. Root cause analysis generated targeted recommendations, including strengthened facility maintenance, digital information and complaint systems, improved service supervision, and optimized security patrols. Novelty: This study integrates SERVQUAL, the Kano Model, and 5 Whys into a systematic framework that identifies priority service attributes while providing root-cause-based improvement strategies for public transportation terminals. Implications: The findings provide practical guidance for terminal management in prioritizing service improvements that address essential passenger needs and support continuous service quality management. Highlights: Overall service performance remained below passenger expectations with a quality score of 0.78. Eight fundamental service attributes were identified as the highest priorities for improvement. Root-cause analysis produced targeted recommendations for operational and facility management. Keywords: 5 Why’s, Kano Model, Passenger Satisfaction, Service Quality